Perceived Parenting Styles of Middle Adolescents in Selected Families at Barangay Kaypian, City of San Jose Del Monte, Bulacan: An Assessment: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Middle adolescence is a life developmental stage where a child faces the process of puberty-related changes. Ages 14-17 are prone to psychological and physical adjustments, andtransitioning from childhood to adolescence may be filled with many challenges andunderstanding. Adolescents start to be more explorative in social, emotional, and cognitivedevelopment aspects. In this time, parents can be a great factor and guidance to help thegrowing children not be missing in the process of being a teenager. The researchers aim todetermine not only the challenges middle adolescents and parents encounter upon creatingparent-child relationships and building potentials but also the factors affecting them, such asadolescent’s autonomy and reliance on their parents. This study was conducted to identifyproblems and shortcomings and is up to create an output to bring solutions for the challengesand persons involved.Results showed that helicopter and positive parenting both cultivate potential among middleadolescents, despite the contrast between the two. It is also revealed that the factors andconflicts presented positively relate to adolescents and parents; however, some of the datashowed academic and child dependency and material needs demands as problems arising.The data was gathered from 50 pairs of respondents, with most of the adolescents being 17with a percentage of 30.Middle adolescents are highly affected by the way parents choose to rear them. Althoughthere are factors or conflicts arising in the parent-child relationship, they could be facedcorrectly if there is guidance from the parent and understanding from the middle adolescent.This study objects to further explore parenting styles, especially the newest type of parentingstyles, and how this matters to the growth of adolescents and their potential. In addition, it is toalso present solutions to the problems the researchers had revealed from the data gathered.
Keywords: Psychology